2017
DOI: 10.1016/j.bbadis.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid sex-dependently affects obesity through linking gut microbiota-driven inflammation to hypothalamus-adipose-liver axis

Abstract: Unraveling the role of dietary lipids is beneficial to treat obesity and metabolic dysfunction. Nonetheless, how dietary lipids affect existing obesity remains unknown. Arachidonic acid (AA), a derivative of linoleic acid, is one of the crucial n-6 fatty acids. The aim of this study was to investigate whether AA affects obesity through associating microbiota-driven inflammation with hypothalamus-adipose-liver axis. Four-week old C57BL/6J mice were fed with a high-fat diet (HFD, 45% fat) for 10weeks to induce o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 53 publications
2
54
2
1
Order By: Relevance
“…DNA extraction and high‐throughput 16S rDNA sequencing were performed as described previously. [ 74 ] Briefly, DNA was extracted from cecum content samples using the MicroElute Genomic DNA Kit (D3096‐01, Omega Bio‐tek, Inc., Norcross, GA) according to the manufacturer's instructions. The total DNA was eluted in 50 μL of elution buffer and stored at −80 °C until PCR measurement (LC‐Bio Technology Co., Ltd., Hang Zhou, Zhejiang, China).…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction and high‐throughput 16S rDNA sequencing were performed as described previously. [ 74 ] Briefly, DNA was extracted from cecum content samples using the MicroElute Genomic DNA Kit (D3096‐01, Omega Bio‐tek, Inc., Norcross, GA) according to the manufacturer's instructions. The total DNA was eluted in 50 μL of elution buffer and stored at −80 °C until PCR measurement (LC‐Bio Technology Co., Ltd., Hang Zhou, Zhejiang, China).…”
Section: Methodsmentioning
confidence: 99%
“…Gut microbiota was analyzed using 16S rDNA sequencing as described previously . Briefly, DNA was extracted from caecal stool samples using a Micro Elute Genomic DNA Kit.…”
Section: Methodsmentioning
confidence: 99%
“…The role of intestinal microbiota should be considered to reconcile the various data on dietary ARA effects on systemic chronic sub-inflammation in obesity, Bowel disease or chronic pathologies proinflammatory. For example, Zhuang et al (2017) recently showed that dietary ARA favour obesity and by acting on the hypothalamus-liver-adipocytes axis but the effect is modulated by sex and intestinal microbiota, female mice being less pejoratively affected. This result should be related to the current work on the relationship between the gut microbiota and Alzheimer's disease (for review see Jiang et al, 2017).…”
Section: Arachidonic Acid In the Current Western Dietsmentioning
confidence: 99%